Extrusion of highly filled flexible polymer sheet. Issue 11 (25th August 2020) - Deshmukh, Shruti; Burbine, Stephen; Keaney, Erin; Banerjee, Shib Shankar; Panwar, Artee; Peters, Christopher; Herndon, Mary; Rockosi, Derrick; Mead, Joey; Barry, Carol
Abstract: Highly‐filled polymer systems include color masterbatches, feedstocks for powder injection molding, and rigid sheets with high levels of flame retardants, but they have not been explored for flexible sheet. This work investigated the (a) selecting a polymer matrix with enough melt strength and flexibility to form a stable sheet with high filler loading, (b) the maximum achievable filler loading for the sheet, and (c) optimizing the process of extruding a highly‐filled flexible polymer system. Extrusion grade low‐density polyethylene (LDPE) provided sufficient flexibility and permitted a maximum filler loading of 36 vol% ( 78 wt%). Good dispersion of the nanoparticle filler, however, required two passes through multiple screw extruders and a small reduction in the viscosity of the LDPE. Sheet with thickness of 415 μm, surface roughness of <1 μm, and sufficient flexibility was extruded continuously at a rate of 10 m/min., but it required a more traditional coat hanger manifold to prevent filler hang up in the sheet die. The filler particles were distributed uniformly through the core and skin of the sheet, giving the sheet good mechanical properties. Abstract :